Friction and wear behavior of Al2O3/rGO fibrous monolithic ceramics with bamboo like architectures. (March 2021) - Chen, Shuna; Su, Yunfeng; Fan, Hengzhong; Song, Junjie; Hu, Tianchang; Hu, Litian; Zhang, Yongsheng
Abstract: Bio-inspired Al2 O3 /rGO fibrous monolithic ceramics with bamboo-like architectures exhibit excellent fracture-resistant behaviors and high structural reliability. The tribological performances and wear mechanisms of these composites were investigated in this study. Results showed that the composites exhibited relatively moderate tribological behaviors with lower and more stable friction coefficients and wear rates compared with monolithic Al2 O3 ceramic. The wear rate can decrease to 1.5 × 10 −8 mm 3 /Nm with a conspicuous drop of more than an order of magnitude. This superior friction-reducing and wear-resistant performance mainly depended on rGO boundaries, which formed discontinuous lubricating films, to reduce direct contact of friction pairs and promote lubricating properties. The influences of fiber cell diameter and applied load on tribological behaviors were also discussed. Highlights: Al2 O3 /rGO fibrous monolithic ceramics with bamboo like architectures were realized. The materials exhibited more stable friction coefficient and much lower wear rate. Fine fiber and high applied load tended to low friction coefficient and wear rate. Friction and wear behavior mainly depended on rGO boundary and grain refinement.